Clinical impact of a multiplex rapid diagnostic pneumonia panel in critically ill patients - Jayda N. Esplund; Alex D. Taylor; Tyler J. Stone; Elizabeth L. Palavecino; Abdullah Kilic; Vera P. Luther; Christopher A. Ohl; James R. Beardsley (Cambridge University Press, 2023)
Abstract Objective: To evaluate the clinical impact of the BioFire FilmArray Pneumonia Panel (PNA panel) in critically ill patients. Design: Single-center, preintervention and postintervention retrospective cohort study. Setting: Tertiary-care academic medical center. Patients: Adult ICU patients. Methods: Patients with quantitative bacterial cultures obtained by bronchoalveolar lavage or tracheal aspirate either before (January-March 2021, preintervention period) or after (January-March 2022, postintervention period) implementation of the PNA panel were randomly screened until 25 patients per study month (75 in each cohort) who met the study criteria were included. Antibiotic use from the day of culture collection through day 5 was compared. Results: The primary outcome of median time to first antibiotic change based on microbiologic data was 50 hours before the intervention versus 21 hours after the intervention (P = .0006). Also, 56 postintervention regimens (75%) were eligible for change based on PNA panel results; actual change occurred in 30 regimens (54%). Median antibiotic days of therapy (DOTs) were 8 before the intervention versus 6 after the intervention (P = .07). For the patients with antibiotic changes made based on PNA panel results, the median time to first antibiotic change was 10 hours. For patients who were initially on inadequate therapy, time to adequate therapy was 67 hours before the intervention versus 37 hours after the intervention (P = .27). Conclusions: The PNA panel was associated with decreased time to first antibiotic change and fewer antibiotic DOTs. Its impact may have been larger if a higher percentage of potential antibiotic changes had been implemented. The PNA panel is a promising tool to enhance antibiotic stewardship.